2013
DOI: 10.1093/jxb/ers376
|View full text |Cite
|
Sign up to set email alerts
|

CONSTANS-LIKE 7 regulates branching and shade avoidance response in Arabidopsis

Abstract: Branching is an important trait of plant development regulated by environmental signals. Phytochromes in Arabidopsis mediate branching in response to the changes in the red light:far-red light ratio (R:FR), the mechanisms of which are still elusive. Here it is shown that overexpression of CONSTANS-LIKE 7 (COL7) results in an abundant branching phenotype which could be efficiently suppressed by shade or a simulated shade environment (low R:FR). Moreover, col7 mutants develop shorter hypocotyls and COL7 overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
76
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 44 publications
3
76
0
1
Order By: Relevance
“…For example, whereas AtCOL3 acts as a flowering repressor during short day and long day conditions, AtCOL9 delays flowering during long days, while AtCOL5 can induce flowering during short days (Cheng and Wang ; Datta et al ; Hassidim et al ). AtCOL7 promotes branching in conditions of a high red light to far‐red light ratio, but enhances shade avoidance syndrome in low red light to far‐red light ratio conditions in Arabidopsis (Wang et al ). However, the characteristics and physiological roles of the products of many of the cloned plant COL genes remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, whereas AtCOL3 acts as a flowering repressor during short day and long day conditions, AtCOL9 delays flowering during long days, while AtCOL5 can induce flowering during short days (Cheng and Wang ; Datta et al ; Hassidim et al ). AtCOL7 promotes branching in conditions of a high red light to far‐red light ratio, but enhances shade avoidance syndrome in low red light to far‐red light ratio conditions in Arabidopsis (Wang et al ). However, the characteristics and physiological roles of the products of many of the cloned plant COL genes remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…An inspection of the current Arabidopsis databases revealed that the expression profiles of many other COL genes are diurnally oscillated (Blasing et al ). Some COL genes have been characterized with reference to functions associated with the regulation of lateral root formation (Datta et al ), branching phenotype, and shade avoidance response (Wang et al ), and the fruit ripening and stress responses in banana fruit (Chen et al ). These results clearly indicate that the CO and COL genes have a wide‐ranging influence on plant development.…”
Section: Introductionmentioning
confidence: 99%
“…These results were consistent with those of a previous study on rice under short-day conditions (Sheng et al, 2016), except for the observed increase in shoot branching. Among A. thaliana CONSTANS-LIKE genes, COL7 reportedly regulates branching and the shade avoidance response involving the PHYBmediated pathway, as well as flowering (Wang et al, 2013;Zhang et al, 2014). Additionally, COL12 overexpression in A. thaliana affects plant architecture by increasing the number of rosette branches and decreasing inflorescence height (Ordonez-Herrera et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several molecular pathways collaborate to promote flowering in higher plants (Moon et al, 2005;He, 2012), which could provide a myriad explanations to the phenology differences in the absence of data from the complex genetic network that regulates flowering. Or else, the COL2 oak gene could be involved in other adaptive function(s) not related to phenology, such as regulation of abiotic stress tolerance through an abscisic acid dependent manner (At-COL4, Min et al, 2015), or regulation of branching patterns and shade avoidance (At-COL7, Wang et al, 2013 (Wolf, 2011). Adaptive introgression of this gene has been inferred in the pair CJAfg-SNEpy, the two oak populations that grow at highest altitude and are exposed to highest solar radiation intensities, further supporting an adaptive role of the PIE082 alleles.…”
Section: Adaptive Introgressionmentioning
confidence: 99%